Examining poly(phenylene sulfide) adhesion using cluster models - Roman, Tanglaw (Animo Repository, 2005)
Density functional theory-based calculations on representative cluster models have been performed to investigate the adhesion strength of poly(phenylene sulfide) (PPS) onto magnesium, silicon and titanium, in addition to previously studied aluminum, copper, silver, and gold. Energy relations of substrate atom interactions with the sulfur end of a PPS monomer showed strongest binding with titanium and aluminum, while the larger transition metals showed the weakest results. A further investigation on the interaction of aluminum with the sulfur atom of a diphenyl sulfide model suggests a strong orientation dependence of the adhesion process, as shown in the greater preference for the in-plane case.